173k views
2 votes
Use the drop-down menus to solve the system using the 5-step process you just learned. x + 6y = 29 2x - 4y = -6 1) Solve for x in the first equation: x =

User Spluf
by
5.4k points

2 Answers

3 votes

Answer:

1. C: -6y+29

2. C: -6y+29

3: 4

4: 5

Therefore, the solution is (x, y) = (5,4)

5: Check Your solution

(5,4) Checks

(5,4) Checks

Explanation:

Did the whole problem on edge

User Lance Kind
by
5.9k points
2 votes
We have the following system of linear equation:

(1)
x+6y=29
(2)
2x-4y=-6

Let's apply elimination method by multiplying (1) by -2, then:


-2(x+6y)=-2(29)

-2x-12y = -58

Next let's subtract (1) and (2):

(1)
-2x-12y = -58
(2)
2x-4y=-6
_______________________

-16y=-64

y=4

Finally, substituting this value in (1) we have that:


x+6(4)=29

\boxed{x=5}
User Karle
by
5.9k points